Diabetes self-management: a qualitative study on challenges and solutions from the perspective of South African patients and health care providers - Tiny Masupe; Sunday Onagbiye; Thandi Puoane; Absetz Pilvikki; Helle Mölsted Alvesson; Peter Delobelle (Taylor & Francis Group, 2022)
Background Health education and self-management are among key strategies for managing diabetes and hypertension to reduce morbidity and mortality. Inappropriate self-management support can potentially worsen chronic diseases outcomes if relevant barriers are not identified and self-management solutions are not contextualised. Few studies deliberately solicit suggestions for enhancing self-management from patients and their providers. Objective This qualitative study aimed to unravel experiences, identify self-management barriers, and solicit solutions for enhancing self-management from patients and their healthcare providers. Methods Eight in-depth interviews were conducted with healthcare providers. These were followed by four focus group discussions among patients with type-2- diabetes and or hypertension receiving chronic disease care from two health facilities in a peri-urban township in Cape Town, South Africa. The Self-Management framework described by Lorig and Holman, based on work done by Corbin and Strauss was used to analyse the data. Results Patients experienced challenges across all three self-management tasks of behavioural/medical management, role management, and emotional management. Main challenges included poor patient self-control towards lifestyle modification, sub-optimal patient-provider and family partnerships, and post-diagnosis grief-reactions by patients. Barriers experienced were stigma, socio-economic and cultural influences, provider-patient communication gaps, disconnect between facility-based services and patients' lived experiences, and inadequate community care services. Patients suggested empowering community-based solutions to strengthen their disease self-management, including dedicated multidisciplinary diabetes services, counselling services; strengthened family support; patient buddies; patient-led community projects, and advocacy. Providers suggested contextualised communication using audio-visual technologies and patient-centred provider consultations. Conclusions Community-based dedicated multidisciplinary chronic disease healthcare teams, chronic disease counselling services, patient-driven projects and advocacy are needed to improve patient self-management.